Computational Design of a Single Amino Acid Sequence that Can Switch between Two Distinct Protein Folds. - Ambroggio, Xavier I.; Kuhlman, Brian (Journal of the American Chemical Society, 2006)
The functions of many proteins are mediated by specific conformational changes, and therefore the ability to design primary sequences capable of secondary and tertiary changes is an important step toward the creation of novel functional proteins. To this end, we have developed an algorithm that can optimize a single amino acid sequence for multiple target structures. The algorithm consists of an outer loop, in which sequence space is sampled by a Monte Carlo search with simulated annealing, and an inner loop, in which the effect of a given mutation is evaluated on the various target structures by using the rotamer packing routine and composite energy function of the protein design software, RosettaDesign. We have experimentally tested the method by designing a peptide, Sw2, which can be switched from a 2Cys-2His zinc finger-like fold to a trimeric coiled-coil fold, depending upon the pH or the presence of transition metals. Physical characterization of Sw2 confirms that it is able to reversibly adopt each intended target fold.